2018
DOI: 10.1002/ejp.1295
|View full text |Cite
|
Sign up to set email alerts
|

A case report of sustained resolution of cancer pain by continuous perineural infusion of local anaesthetic

Abstract: This case report provides new insights into the treatment of cancer pain. The most interesting finding is that the pain did remained absent after 45 days of continuous infusion of local anaesthetics through an interscalene catheter. We postulated that local anaesthetic drugs have an impact on pain memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…29 A previous study also showed that anesthetics exerted direct or indirect effects on the body’s immune system, thereby regulating immune activity. 30 Studying the effects of different anesthetics on immune cells might be useful for guidance of clinical anesthesia. In this study, we found that the main killing effector molecule GZMB in peripheral blood NK cells of patients with gastric cancer who were anesthetized with propofol showed significantly higher expression than that of patients who were anesthetized with sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…29 A previous study also showed that anesthetics exerted direct or indirect effects on the body’s immune system, thereby regulating immune activity. 30 Studying the effects of different anesthetics on immune cells might be useful for guidance of clinical anesthesia. In this study, we found that the main killing effector molecule GZMB in peripheral blood NK cells of patients with gastric cancer who were anesthetized with propofol showed significantly higher expression than that of patients who were anesthetized with sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%